Arousal-Mediated Sleep Disturbance Persists During Cocaine Abstinence in Male Mice - Bjorness, Theresa E.; Greene, Robert W. (Frontiers in Neuroscience, 2022)
Acute cocaine disturbs sleep on a dose-dependent basis; however, the consequences of chronic cocaine remain unclear. While the arousal promotion following cocaine has been well-established, effects of cocaine on sleep after termination of chronic cocaine exposure appear variable in human subjects with few studies in non-human subjects. Here, a within-subjects design (outcomes normalized to baseline, undisturbed behavior) and between-subjects design (repeated experimenter-administered cocaine vs experimenter-administered saline) was used to investigate sleep homeostasis and sleep/waking under repeated cocaine/saline exposure and prolonged forced abstinence conditions in mice. Overall, during the forced abstinence period increases in arousal, as determined by sleep latency and gamma energy, persisted for 2 weeks. However, the sleep response to externally enforced sleep deprivation was unchanged suggesting that sleep disruptions during the forced abstinence period were driven by enhancement of arousal in the absence of changes in sleep homeostatic responses.